DEVELOPMENT OF YOUTH IDENTITY AND I-CONCEPT - Vynar , Valentyna (The Modern Higher Education Review, 2022)
The article is devoted to the psychological phenomenon of identity and self-concept, the peculiarities of their formation and development in early youth. An attempt was made to compare different interpretations of the concept of identity, the main aspects and types of identity were considered. Various approaches of domestic and foreign scientists to the problem of identity formation are analysed. A psychological analysis of scientific approaches to the problem of the formation and development of identity during the period of personality maturation was carried out. The main mechanisms of the formation of self-identity in the process of ontogenetic development of the personality are highlighted. The results of the study of social roles and individual characteristics (family, interpersonal, individual-age, educational-professional, personal-civic, personal-individual) are presented, the ratio of types of personal identity and the level of awareness and acceptance of them are determined. It is shown that identity is an integral component of a person’s personal development, the result of self-awareness and self-determination of one’s "I". The result of these processes is a dynamic system of a person’s ideas about himself, evaluations of his actions, thoughts, feelings, morality and interests, ideals and motives of behaviour, a holistic assessment of himself as a person, his place in life, a sense of the personal value of everything that is included in the sphere "I". The study of the psychological foundations of this concept is important for self-development, self-actualization of the individual, which contributes to the formation of a mature, and later professional identity of the individual.